The Role of Teachers in Implementing the Independent Curriculum at Baitul Ilmi IT Middle School - Reza Fauzi Rasyad; Mohamad Erihadiana (al-Afkar, Journal For Islamic Studies, 2024)
This research examines the role of teachers in implementing an independent curriculum. The aim of this research is to find out related matters and how teachers play a role in the independent curriculum at Baitul Ilmi Cianjur IT Middle School. This research uses a qualitative descriptive analysis method using data collection, processing and analysis techniques related to the Role of Teachers in the Implementation of the Independent Curriculum. The results obtained are that teachers have an important role in improving the quality of learning by using an independent curriculum. Teachers are expected to create effective, meaningful and quality learning. One of the efforts made by the Baitul Ilmi IT Middle School to optimize the role of teachers in the implementation of the independent curriculum is to socialize all teachers, students and parents of students about SMEs, include SMI training for teachers, make adjustments to learning administration in accordance with SMI guidelines, plan the Pancasila Student Profile Strengthening Project (P5), adjust school and Islamic boarding school programs, and take part in the National Assessment and study environment surveys that can support it. This effort has at least an impact on the learning process even though its implementation has not been fully fulfilled.